CSC software corrects off-target mediated gRNA depletion in CRISPR-Cas9 essentiality screens - Alexendar R. Perez (Nature Portfolio, 2021)
Off-target effects often confound the interpretation of CRISPR screens. Here, the authors introduce a computational method that corrects for off-targets in gRNA depletion assays, circumventing the need to completely discard unspecific guides.